Managing change in performance measures: An inter-company case study approach - Mohammed Salloum; Stefan Cedergren (International Journal of Business Science & Applied Management (IJBSAM), 2012)
The field of performance measurement and management (PMM) is well filled with frameworks, models and guidelines addressing what to measure and how to design a performance measurement system (PMS). However, what has been less examined so far is how to ensure that PM evolve in tandem with their environments. Further, the few approaches available today are prescriptive and outlines how or what practitioners should do in order to manage change in their PM. Thus, a gap exists in understanding how organisations manage change in their PM in practice. Thus, the purpose of this paper is to outline and compare the approaches of three case companies for managing PM change. In order to fulfil the purpose of the paper, the data presented has been collected through the deployment of case studies. The choice of case studies as means for data collection stems from the possibility of an in-depth and holistic examination of the formulated phenomenon. All three case companies belong to the same company-group that operates within the transportation industry. The industrial footprint of the company is global with operations and sales spread out over the world. The findings suggest that all three companies have processes in place for managing change in PM. However, the approaches differ in design and context. Even though the case companies had different approaches in place to manage change in PM, they shared several commonalities. Commonalities were shared in the way of execution, process input and challenges in IT and culture. Furthermore, employee involvement seemed to be the biggest challenge for all three companies. The findings put forward in this paper are limited as they are confined to three companies from the same company-group. More studies, both from within and outside the company-group, are needed in order to establish a solid base of empirical data for generalisation. However, this paper makes a contribution both through describing how three companies manage PM change and through elaborating on the underlying factors affecting functionality.
Keywords: 650; performance measurement; performance measurement systems; performance management